Stereotypy i uprzedzenia jako determinanty jakości życia kobiet - Miluska, Jolanta (Wydział Prawa i Administracji UAM, 1993)
The article presents the results of research on sex stereotypes which may lower the perception of t h e quality of life of employed women. The results prove that there are no negative stereotypes and prejudice against women. Therefore, it can be said that the level of fear of unemployment should not be higher in the case women than it is in the case of men.
Sexual stereotypes and prejudice as determinants of the quality of life of women